Car wash water recycling system - Nawawi, Muhammad Amirul; Kamisan, Muhamad Nurul Fitri; Adam, Nur Farah Aqilah; Tuan Ibrahim, Tuan Mohd Hafeez; Ismail, Fadillah (Penerbit UTHM, 2020)
The high rate of transportation and vehicle washing centers led to an increase in water consumption. When the water consumption increase, the amount of wastewater discharged and the cost of utility will also increase. Only the right technique used for washing the vehicles can minimize the amount of water consumption. Conservation of water will not only save the water supply, but it will also help in financial savings. Recycling and reusing the water from the car wash means collecting, processing, and treating the contaminated water to remove the dirt and contaminants and using the treated water again for car washing. As cars body always stained with dirt and dust while driving, some dirt such as small stones might stuck and penetrate into the wheels and caused major damage. Thus, a regular car wash usually is needed for every vehicle to avoid this problem. Moreover, getting a regular car wash can also improve car performance. Hence, periodically car washing is one of the best ways to preserve and maintain the performance of vehicles.